INSECT-PATHOGEN RELATIONS IN THE PROBLEM OF THE YELLOWING OF THE POTATO VEINS - DIAZ, MARTHA CECILIA; PULGARIN, JOSE M.; SALDARRIAGA-V., ALFREDO (Revista Colombiana de Entomología, 1990)
"Potatoes yellow vein" is a troublesome disease in Colombia (Antioquia and Nariño) as well as in Ecuador where losses can reach up to 50% of the yield. The greenhouse whitefly (Trialeurodes vaporariorum) is known to be the vector. However, since some information is lacking regarding the pathogen-vector relationships, this research was conducted at the Experiment Station "La Selva" (Rionegro, Antioquia), and the results were as follows; 1.- One single whitefly is able to transmit the disease. A maximum, effectivity is achieved with twenty whiteflies. 2.The acquisition period has a minimum of one hour, effectivity increases as time increases, up to a maximum of six hours. 3.- Minimum inoculation time: one hour. 4.- No incubation period in the vector was detected when both acquisition and inoculation were tested in 24 hours. 5.- Pathogen retention in the vector reached a maximun of six days. 6.- Disease incubation lasted between 13 and 25 days. 7.- This is an example of a semi-persistent transmission.